Privacy-preserving access control for public wireless LAN utilizing the bitcoin blockchain - Yukun NIU; Lingbo WEI; Chi ZHANG; Xia ZHANG; Vejarano Gustavo (网络与信息安全学报)
In designing an access control scheme for public wireless LAN (WLAN),user privacy protection and user accountability are two conflict goals.A novel user management and access control scheme was proposed to solve this problem by utilizing the bitcoin blockchain and Intel SGX.It utilized unmodified bitcoin blockchain to manage the ownership of access credentials for users without relying on any trusted third party.It adopted Intel SGX-based mixing technology to enhance anonymity of users’ access credentials.It designed verification path rule to resolve the conflicts between the privacy-preserving and accountability objectives.The effectiveness and feasibility of the proposed scheme are also demonstrated by security analysis and performance evaluation.